Ti3C2TX encapsulation of CTAB-functionalized polypyrrole nanospheres towards pseudocapacitive intensification in supercapacitors - Poh, Wen Siong; Hoo, Do Yee; Zheng, Sheng Qiang; Ong, Wee-Jun; Khiew, Poi Sim; Lim, Hong Ngee; Foo, Chuan Yi (Elsevier, 2024)
The critical criteria for supercapacitor to power the increasingly prevalent portable electronic devices lies within its active material design that yields high specific capacitance without compromising rate performance. Herein, polypyrrole (PPy) was synthesized into nanospheres (PPy NS) to improve bulk ion transport kinetics. However, numerous interfaces generated by nanospherical structure induce high nanocontact resistance, resulting in low specific capacitance. Thus, PPy NS were surface-functionalized with cationic surfactant n-Cetyl-n,n,n-trimethylammonium bromide to facilitate enwrapping by highly electrically conductive Ti3C2TX nanosheets via electrostatic self-assembly, where the Ti3C2TX shells serves as effective conductive pathways. Flake sizes of Ti3C2TX nanosheets were modulated via probe ultrasonication to maximize conformability to PPy NS, minimizing tortuosity of ion diffusion pathways and establishing ubiquitous heterostructure contact. This resulted in enhanced rate performance of 74 % capacitive retention during scan rate increase from 1 to 100 mV s−1 (pure PPy NS at 58 %). Furthermore, positively charged moieties imparted by surface-functionalization of PPy NS instigate electronic coupling with negatively charged surface terminations of Ti3C2TX nanosheets, facilitating rapid interfacial electron transfer. Through simultaneous dimensional and surface charge alignment, the nanocomposite achieved specific capacitance of 619.7 F g−1 at 5 A g−1 (∼37-fold enhancement over pure PPy NS), despite incorporation of low amounts of Ti3C2TX (9 wt%). This work highlights the potential of such material integration techniques in realizing capacitive intensification beyond incremental improvements as well as boosting rate performance, with methodical employment of minimal functional additive. It serves as a framework for future studies optimizing 2D-0D material nanocomposites for supercapacitor applications. © 2024 Elsevier B.V.